2019
DOI: 10.1002/cplu.201800640
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic Diarylethenes Designed for Surface Deposition: From Self‐Assembled Monolayers to Single Molecules

Abstract: The efficient switching that can occur between two stable isomers of diarylethenes makes them particularly promising targets for opto‐ and molecular electronics. To examine these classes of molecules for electronics applications, they have been subjected to a series of scanning tunneling microscopy (STM) experiments, which are the focus of this Review. A brief introduction to the chemical design of diarylethenes in terms of their switching capabilities along with the basics of STM are presented. Next, initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 116 publications
(253 reference statements)
0
3
0
Order By: Relevance
“…Photochromic molecules have also been applied as a "switch" for property modulation of self-assembled monolayers (SAMs). [98][99][100][101][102][103] The SAMs were formed on Au-stripped substrates using a spiropyran derivative, H 2 SPDT (H 2 SPDT = 2-(3′,3′-dimethyl-6-nitrospiro[chromene-2,2′-indolin]-1′-yl)ethyl 6,8-dimercaptooctanoate; c = 1; Figure 11), through immersing the Au surface in an ethanol solution of H 2 SPDT. [96] The thickness of the resulting photochromic SAM was estimated to be 15.4 ± 2 Å, and quantitative analysis using XPS suggested that 38% of the spiropyran molecules undergo photoisomerization to merocyanine.…”
Section: D Materials (D = 2) With Covalently Integrated Photochromic ...mentioning
confidence: 99%
“…Photochromic molecules have also been applied as a "switch" for property modulation of self-assembled monolayers (SAMs). [98][99][100][101][102][103] The SAMs were formed on Au-stripped substrates using a spiropyran derivative, H 2 SPDT (H 2 SPDT = 2-(3′,3′-dimethyl-6-nitrospiro[chromene-2,2′-indolin]-1′-yl)ethyl 6,8-dimercaptooctanoate; c = 1; Figure 11), through immersing the Au surface in an ethanol solution of H 2 SPDT. [96] The thickness of the resulting photochromic SAM was estimated to be 15.4 ± 2 Å, and quantitative analysis using XPS suggested that 38% of the spiropyran molecules undergo photoisomerization to merocyanine.…”
Section: D Materials (D = 2) With Covalently Integrated Photochromic ...mentioning
confidence: 99%
“…A photochromic molecule adsorbs light at specific wavelengths and thus appears with convertible colors [2,5]. Concomitant with color changes, their physical and chemical properties, such as molecular geometry, dipole moment and electronic structure, alter with isomerization and show switchable on and off states [5][6][7]. The interest in photoswitchable molecules is large and covers diverse research fields ranging from nanomachines (rotaxane-based molecular machines [8][9][10], light-driven rotary molecular motors [11,12]), photoactive nanoparticles (noble metal Nps [13][14][15], fluorescent Nps [16,17]), nanoelectronics [7] (photoactive molecular junctions [18][19][20][21][22], rectifiers [23], memories [24,25] or organic field effect transistors [25,26]), metal organic nanoassemblies (photoswitchable metal-organic molecular cage [27] or metal-organic frameworks [28,29]), supramolecular self-assembled systems (light-driven supramolecular amphiphiles [30], supramolecular polymers [31,32]), biological nanosystems [5,33] and pharmacology [34].…”
Section: Introductionmentioning
confidence: 99%
“…A photochromic molecule adsorbs light at specific wave-lengths and thus appears with convertible colors [2,5]. Concomitant with color changes, their physical and chemical properties, such as molecular geometry, dipole moment and electronic structure, alter with isomerization and show switchable on and off states [5][6][7]. The interest in photo-switchable molecules is large and covers diverse research fields ranging from nanomachines (rotaxane-based molecular machines [8][9][10], light-driven rotary molecular motors [11,12]), photoactive nanoparticles (noble metal Nps [13][14][15], fluorescent Nps [16,17]), nanoelectronics [7] (photoactive molecular junctions [18][19][20][21][22], rectifiers [23], memories [24,25] or organic field effect transistors [25,26]), metal organic nanoassemblies (photoswitchable metal-organic molecular cage [27] or metal-organic frameworks [28,29]) supramolecular self-assembled systems (light driven supramolecular amphiphiles [30], supramolecular polymers [31,32]), biological nanosystems [5,33] and pharmacology [34].…”
Section: Introductionmentioning
confidence: 99%